(untitled) (Journal of Psychiatrists’ Association of Nepal, 2019)
Introduction: Cognitive deficits in bipolar disorders persist after the subsidence of active symptoms. This study was carried out to assess the working memory of patients with bipolar disorder in euthymic state. Material And Method: Forty euthymic bipolar patients attending a tertiary care mental hospital with equal number of matched controls in terms of age, sex and education were included in the study. Working memory assessments was done using WAIS-III digit span subtest. Results: The mean of total digit span test for case group was 8.48±2.04 similarly it was 10.33±2.32 for the controls. The result showed that the mean digit span of cases and control groups are significantly different (p value of < 0.01). The Pearsons correlation between the clinical variables and working memory test in euthymic bipolar patients (case group) was found that the total score for digit span test was negatively correlated with all other clinical variables However, this correlation was found to be non-significant. Conclusion: The working memory impairment persists in remitted bipolar disorder patients and this may represent underlying trait abnormality not the state abnormality.